STRATEGI PEMERINTAH KABUPATEN MOJOKERTO UNTUKMENINGKATKAN KUALITAS PELAYANAN DI SEKTOR PARIWISATA (Studin Pada Dinas Pemuda, Olahraga, Kebudayaan dan Pariwisata Kabupaten Mojokerto) - Mahfudi, Andri (Universitas 17 Agustus 1945 Surabaya, 2016)
Sector Tourism sevice is one of the effort that can improve tourism interprice in those area. This research is to know and always the tourism condition, strategy to improve the sector tourism service done by public young service, sport, culture and tourism of Mojokerto district. But tourism sector still has some obstacle so is is need some strategies to improve the quality of service by the district goverment at tourism in Mojokerto. To know the strategy to improve the quality of tourism sector service, so in this research , the researcher used qualitative method with description approach. Based on the research, the researcher found that there were there strategies which were used by the public young service, sport, culture and tourismof Mojokerto district to improve the quality of the tourism sektor service. Those were improve the tourism, tourism promotion, and contruction tourism interprise. But in those strategies still have some obstacles whether internal or external obstacle.Key words : Strategy, Tourism Service, Quality of Service.